2022
DOI: 10.1186/s13287-022-02856-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in cancer therapy: the Pandora's Box of cancer stem cells

Abstract: Drug resistance is the main culprit of failure in cancer therapy that may lead to cancer relapse. This resistance mostly originates from rare, but impactful presence of cancer stem cells (CSCs). Ability to self-renewal and differentiation into heterogeneous cancer cells, and harboring morphologically and phenotypically distinct cells are prominent features of CSCs. Also, CSCs substantially contribute to metastatic dissemination. They possess several mechanisms that help them to survive even after exposure to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 155 publications
(222 reference statements)
1
40
0
Order By: Relevance
“…A reduction in RUNX1 transcriptional activity significantly improves the efficacy of Px and Enza in forced suspension culture (Figure 6). Under these conditions we had to use higher doses of all the drugs, including RUNX1 inhibitor, to achieve a reduction in cell viability rate similar to the one obtained in standard adherent cultures (Figure 6), validating the already known concept that CSC populations are more resistant to treatment [42]. S3.…”
Section: Reduction In Runx1 Transcriptional Activity Decreases Mda-mb...supporting
confidence: 68%
“…A reduction in RUNX1 transcriptional activity significantly improves the efficacy of Px and Enza in forced suspension culture (Figure 6). Under these conditions we had to use higher doses of all the drugs, including RUNX1 inhibitor, to achieve a reduction in cell viability rate similar to the one obtained in standard adherent cultures (Figure 6), validating the already known concept that CSC populations are more resistant to treatment [42]. S3.…”
Section: Reduction In Runx1 Transcriptional Activity Decreases Mda-mb...supporting
confidence: 68%
“…At the same time, external energy can realize the controlled release of nano-drugs based on metal ions and mediate synergistic treatment. Besides, it has been confirmed that most tumor cells are not resistant to metal ions [ 282 ], which enables metal ions to apply to multi-course treatment. Further, the metal ion-mediated cancer diagnosis is conducive to monitoring and controlling the therapeutic process, improving treatment efficiency.…”
Section: Summary and Prospectmentioning
confidence: 99%
“…Moreover, these CSCs acquire multidrug resistance, thus protecting themselves from most traditional chemotherapeutic agents. As a result, this small subpopulation of persistent cells forms more aggressive and chemoresistant tumors, resulting in the failure of cancer therapy [ 9 ]. Thus, identifying and targeting these rare cancer cells are believed to be important for understanding the etiology of cancer and developing a novel therapeutic strategy for cancer therapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%